Targeting cardiovascular and metabolic risk modification in end stage renal disease (ESRD): a randomized controlled clinical trial on niacin’s effects on lipoprotein(a) and biochemical markers in hemodialysis patients - Galal, Amira Reda Muhammad; Salah, Maha Abdel Rhman; Binsaleh, Ammena Y.; Alsubaie, Nawal; Alrossies, Amani S.; Elthakaby, Ahmed Hassan; Elsawy, Ghadir Mohamed; Ali, Azza A.; Zalat, Zeinab Al Kasaby (Frontiers in Medicine, 2025)
BackgroundEnd-stage kidney disease (ESRD) patients on dialysis face pronounced cardiovascular and metabolic risks due to disruptions in lipoprotein(a), phosphorus, potassium, uric acid, and lipid balance. Current therapeutic options offer limited capacity to address these multifaceted abnormalities. Niacin is unique in this regard, as it not only lowers lipoprotein(a) but also influences phosphorus and uric acid metabolism. This study evaluates the efficacy of niacin therapy in improving these biochemical markers, thereby addressing an important therapeutic gap in this vulnerable population.MethodsIn a randomized, controlled trial, 50 hemodialysis patients were divided into two groups of twenty-five each. The control group continued standard care, while the niacin group received 500 mg/day niacin alongside standard therapy. Patients were followed for 3 months.ResultsSystolic and diastolic blood pressure were stabilized by niacin administration, in contrast to the control group, where both parameters rose significantly. Phosphorus decreased significantly in the niacin group (5.59 to 4.85 mg/dL, P = 0.0077), while increasing in controls. PTH levels decreased by 60% with niacin but rose by 41.6% in controls (P = 0.001). Potassium levels fell by 27% in the niacin group, whereas they rose by 23.9% in controls. Sodium remained stable with niacin but declined in controls. Uric acid levels rose sharply in controls but remained stable with niacin. Niacin significantly improved lipid profiles, notably reducing LDL (31.9% vs. 7.9%) and total cholesterol (13.3% vs. 3.7%). Although triglycerides and VLDL rose in both groups, these variations were not of statistical significance. Importantly, Lp(a) levels decreased by 11.4% in the niacin group.ConclusionNiacin (500 mg/day) offers significant cardiovascular and metabolic benefits for hemodialysis patients, supporting its role as an adjunctive therapy in managing ESRD-associated risks.Clinical trial registrationhttps://clinicaltrials.gov/, NCT06406140